Come Out, Get Out: Relations Among Sexual Minority Identification, Microaggressions, and Retention in Higher Education**Other manuscripts, which utilize the full dataset and propose distinct research questions pertaining to a separate set of measures, have been submitted for publication elsewhere. All relevant federal and institutional research ethical standards have been met regarding the treatment of participants. - Crane, Phoenix R. (Journal of interpersonal violence, 2022)
Heterosexism, in the form of microaggressions, contributes to hostile, anti-lesbian, gay, bisexual, transgender, and queer (LGBTQ) college campus climates, thereby limiting sexual and gender minority students? social engagement and academic persistence. Using Tinto?s model of institutional departure, we examined the degree to which experiencing microaggressions affects sexual minority college students? retention as a function of their feelings of discomfort in the classroom. Mediation analyses were performed on a subsample of data from 152 self-identified LGBTQ college students at a southern university in the United States to examine relations among experiences of self-reported microaggressions, self-rated classroom discomfort, and expressed intentions to transfer from the university. Self-reported discomfort in the classroom accounts for the relation between experiences of microaggressions and LGBTQ students? intentions to transfer from the university. Specifically, LGBTQ students who experienced microaggressions more often reported greater discomfort in their classrooms and reported fewer intentions to continue studying at their university. Universities should strive to implement campus-wide programs that help minimize microaggressions, encourage cultural competency and comfort in the classroom, and combat anti-LGBTQ prejudice to better support students in their day-to-day academic endeavors. LGBTQ students who feel safe and supported in the classroom may be protected from heterosexism and social isolation and, thereby, may be more likely to persevere in their academic pursuits.